New Zealand exporter - Export Institute of New Zealand (Auckland, N.Z. : Richards Pub., 1981)
Quality control and orderly export marketing take on special significance for New Zealand.
includes index and maps
II 17/01/2019
Loans
Keywords: Manufacturing industries; Foreign trade promotion; Exports; Commerce; Exports; Foreign trade promotion; Manufacturing industries; New Zealand; New Zealand